2008
DOI: 10.1111/j.1525-1594.2008.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Conjunction With Milrinone Better Stabilized Pulmonary Hemodynamics After Fontan Procedure

Abstract: Inhaled nitric oxide (iNO) has been used for patients with increased pulmonary vascular resistance (PVR) shortly after Fontan operation, but repeat deterioration of PVR during or shortly after its withdrawal remains a major concern. Milrinone, a phosphodiesterase type 3 (PDE3) inhibitor, can also reduce PVR for postoperative patients with pulmonary hypertension. We hypothesized that iNO, in conjunction with milrinone, can provide additive benefits for pulmonary hemodynamics and reduce the occurrence of iNO wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Currently phase III trials are underway. Similar improvements in pulmonary hemodynamics have been reported when inhaled nitric oxide was combined with milirinone, a PDE-3 inhibitor (53). And finally there are several drugs currently undergoing clinical trials that are targeted at stimulating NO-independent soluable guanylyl cyclases.…”
Section: Nitric Oxide Pathway and Pahsupporting
confidence: 73%
“…Currently phase III trials are underway. Similar improvements in pulmonary hemodynamics have been reported when inhaled nitric oxide was combined with milirinone, a PDE-3 inhibitor (53). And finally there are several drugs currently undergoing clinical trials that are targeted at stimulating NO-independent soluable guanylyl cyclases.…”
Section: Nitric Oxide Pathway and Pahsupporting
confidence: 73%
“…We did not administer NO during the operation because we planned early extubation suitable for the Fontan circulation, and repeated the deterioration of PVR after its withdrawal remained a concern. Cai et al [8] reported that the combined use of NO and milrinone optimally stabilized the pulmonary hemodynamics after a Fontan operation.…”
Section: Discussionmentioning
confidence: 98%
“…In both series, the infants were already receiving iNO at the time that the milrinone was started, and significant improvements in oxygenation were observed with milrinone treatment (Bassler et al 2006; McNamara et al 2006). Similarly, in pediatric patients ( n = 46, average age 5 years) undergoing a Fontan procedure, postoperative use of milrinone in conjunction with iNO resulted in greater improvements in the transpulmonary gradient and arterial oxygen saturation versus those children treated with iNO alone or milrinone alone (Cai et al 2008a, b). These clinical case series all support an interesting potential role for milrinone in the treatment of neonatal pulmonary hypertension, especially when used in conjunction with iNO.…”
Section: Pde Inhibitors In Neonatal Pulmonary Hypertensionmentioning
confidence: 95%